Pregnancy outcome following cervical cerclage: a four-year review. (16th November 2010) - Edoo, AWI; Nor, NA Mat; Bozreiba, N; Fahy, U
Abstract : The aim was to assess pregnancy outcome in women who had an elective cervical cerclage. This was a 4 year retrospective case note review. The study group comprised singleton pregnancies where an elective cervical cerclage was inserted. 53 cases were identified. Cervical cerclage was inserted on the basis of obstetric history. Rescue cerclage and multiple pregnancies were excluded. There were 47 McDonald and six Shirodkar sutures performed. Gestation at cervical cerclage insertion ranged from 12 to 19 weeks. High vaginal swab was performed in 35 cases prior to insertion of cerclage and only two were positive for infection (BV). 7.5% (4/53) women had a mid trimester spontaneous abortions. Preterm delivery rate was 15% all of which delivered vaginally. There was one neonatal death and one intrauterine death at 24 and 25 weeks, respectively. Gestational age at delivery ranged from 24+ weeks to 40+ weeks. The take home baby rate was 47/53 (88.7%). There were 10 elective caesarean section and 37 vaginal deliveries. In the subgroup of patients who had cervical suture removed electively, time interval from removal to delivery range from 1 to 30 days. Mean length of labour was 5 h 11 min SD±2 h 35 min. This study shows that cervical suture is an effective and relatively safe procedure for the prevention of preterm labour. The success rate is comparable to reported efficacy rate in the literature.